Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acs.jpca.7b11945
|View full text |Cite
|
Sign up to set email alerts
|

Design of Exceptionally Strong Organic Superbases Based on Aromatic Pnictogen Oxides: Computational DFT Analysis of the Oxygen Basicity in the Gas Phase and Acetonitrile Solution

Abstract: DFT B3LYP calculations convincingly showed that aromatic pnictogen oxides offer scaffolds suitable for tailoring powerful organic superbases exhibiting exceptional oxygen basicity in both the gas phase and polar aprotic acetonitrile solution. With their protonation enthalpies and pK values, they surpass the basicity of classical proton sponges and related nitrogen bases. The most potent system is provided with two arsenic oxide moieties on the phenanthrene framework assisted by the two phosphazeno groups in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…For example, a recent study on the simple pnictogen oxides shows that the PA of the oxygen atom in these compounds increases as As–O > N–O > P–O. 33…”
Section: Resultsmentioning
confidence: 99%
“…For example, a recent study on the simple pnictogen oxides shows that the PA of the oxygen atom in these compounds increases as As–O > N–O > P–O. 33…”
Section: Resultsmentioning
confidence: 99%
“…The expansion of π‐system in ketene 9 using the cyclohexadiene and cyclopropene rings causes its PA to increase drastically close to the hyperbasicity limit (hyperbases are called compounds with PA ≥ 1,255.2). [ 43 ] The increments in HOMA values of three‐ and six‐membered rings in the conjugate acid of ( 9+H ) + compared with the neutral molecule 9 to the amounts of 0.46 and 1.05, respectively, point out to the positive charge delocalization in these rings and cation stability. The increasing NICS values associated with the protonated form of ( 9+H ) + for both rings, also testifies to this.…”
Section: Resultsmentioning
confidence: 99%
“…Diverse potential applications of the superbases in different fields such as the catalytic applications has always been an impetus in chemistry. During the recent years, a lot of experimental and theoretical studies have been reported on design of the strong organosuperbases and new proton sponges . This is not surprising due to two reasons including: 1) acid‐base chemistry is one of the main research fields in chemistry, 2) the advantages of the organosuperbases are based on their better solubility in the organic solvents, moderate conditions of reaction and their excellent stability .…”
Section: Introductionmentioning
confidence: 99%